DNA–Polymer Nanostructures by RAFT Polymerization and Polymerization‐Induced Self‐Assembly - Lückerath, Thorsten (Angew Chem Int Ed Engl, 2020)
Nanostructures derived from amphiphilic DNA–polymer conjugates have emerged prominently due to their rich self‐assembly behavior; however, their synthesis is traditionally challenging. Here, we report a novel platform technology towards DNA–polymer nanostructures of various shapes by leveraging polymerization‐induced self‐assembly (PISA) for polymerization from single‐stranded DNA (ssDNA). A “grafting from” protocol for thermal RAFT polymerization from ssDNA under ambient conditions was developed and utilized for the synthesis of functional DNA–polymer conjugates and DNA–diblock conjugates derived from acrylates and acrylamides. Using this method, PISA was applied to manufacture isotropic and anisotropic DNA–polymer nanostructures by varying the chain length of the polymer block. The resulting nanostructures were further functionalized by hybridization with a dye‐labelled complementary ssDNA, thus establishing PISA as a powerful route towards intrinsically functional DNA–polymer nanostructures.